TRANSFORMATIONAND POLICY PROBLEMS ISLAMIC EDUCATION - M. Kasyful Anwar; Sabran; Sri Susmiati (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2026)
This study examines the dynamics and challenges in the implementation of Islamic education policies across various levels of education in Indonesia, ranging from primary education to higher education. Using a descriptive qualitative approach, the study analyzes how these policies contribute to national education goals and address structural issues within the education system. The findings reveal that despite the existence of systematic regulations, significant challenges remain, including the uneven distribution and quality of educators, disparities in facilities between urban and rural areas, unstable curricula, and weak institutional coordination. These issues are further exacerbated by limited professional training opportunities and inadequate integration of Islamic values and religious moderation. The authors propose several solutions, including the digitalization of Islamic education, strengthening teacher competencies, implementing context-based curriculum reforms, and enhancing community engagement. The study highlights the importance of participatory and locally responsive policy reforms to improve the quality and relevance of Islamic education in Indonesia. The implications of this study suggest that adaptive and sustainable policy implementation can enhance the quality of Islamic education, promote equitable access to educational opportunities, and support the development of competent, moderate, and character driven learners in accordance with the goals of national education. The implication of implementing these policy recommendations has the potential to improve the quality of learning processes and outcomes, expand access to more equitable Islamic education, reduce the gap in education quality between regions, and strengthen the pedagogical and professional strength of teachers.